Acute appendicitis: is it a seasonal disease? - Elshambaty, Yasir Babiker; Alzahrani, Saleh A.; AlOmari, Talal A.; Shahwan, Waleed S.; Alzahrani, Abdullah A.; Alghamdi, Osama A. (International Journal Of Community Medicine And Public Health, 2021)
Background: The aim of this study was to review the management of acute appendicitis in a rural hospital. It was generally reported to be more common in men. Appendicitis is the most common surgical cause of abdominal pain worldwide. Appendectomy is the lonely curative treatment of appendicitis. Methods: This was a retrospective study in which we reviewed the records of the patients who had been diagnosed and operated on for appendicectomy from January to December 2017 in a rural hospital. The data were analyzed with SPSS version 25. Results: The total number of the patients was 114. About 69.3% are males. The mean age was 25.11 years. About (39.5%) were above 20 years old. Most of the cases presented in the period between January and March (27.3%). Right lower quadrant pain was the most common presenting symptom (93.9%). Nausea and vomiting mentioned by 57 (50%) and 74 (64.9%) of the participants respectively, fever in 42 (36.8%), muscle guarding in 0.9%, tenderness in 44 (38.6%), abdominal ultrasound was requested in 96 (84%). The most common histological diagnosis was acute suppurative appendicitis with peri-appendicitis in 15 (13.2%). All the cases were treated with open appendicectomy. Conclusions: We concluded that male are more affected with acute appendicitis. The most common presenting symptom was right lower quadrant pain. The vast majority of the cases were in the winter. Ultrasound has been used in the most cases particularly in male more than in females. The most common histological diagnosis was acute suppurative appendicitis. Open appendicectomy is the main operative management in our pts.